Lifetime breeding-site and nest-site fidelity in a declining terrestrial toadlet: evidence for a win-stay/lose-shift strategy - Byrne, Phillip G.; Silla, Aimee J. (Frontiers in Conservation Science, 2023)
Breeding-site fidelity can occur at various spatial scales and can vary in strength across these scales. Understanding this variation, and rules governing individual site-fidelity decisions, can have important implications for the conservation and management of threatened species.Globally, amphibians are in rapid decline and breeding-site fidelity appears to be widespread, yet few studies have investigated patterns of lifetime breeding-site fidelity, and no studies have explored decision-making rules in situ. We investigated lifetime patterns of breeding site fidelity in the brown toadlet Pseudophryne bibronii, a species displaying population declines and local extinction throughout its range. We monitored a single population for a period spanning 10 years to establish the extent that males express site fidelity at the scale of the breeding site and the breeding patch. We also examined male nest-site fidelity between breeding years in relation to mating success to examine if toadlets follow a Win-stay/Lose shift strategy. Overall, we found that males displayed extreme lifetime fidelity to specific breeding patches within the breeding site, but that males regularly moved nest-site locations between breeding years. The degree of nest-site fidelity was related to male-mating success, whereby successful males established nests closer to a previous years' nest location than unsuccessful males. Our findings suggest that brown toadlets display extreme site fidelity at the scale of the breeding patch, but that within patches male nesting decisions are flexible and follow a win-stay/lose-shift strategy. These results provide novel evidence that breeding site fidelity in amphibians can vary depending on spatial scale (indicative of scale-dependent information use) and that a rule-based learning strategy can influence the degree of nest-site fidelity. Breeding patch fidelity and capacity for spatial learning may be widespread in longlived amphibians and necessitate in situ conservation strategies that protect known breeding patches (and adjacent habitat) whilst enabling unconstrained localised movement.